Optimization of Processing Parameters of Soy-Sorghum Blends Extrudates - Singh, Daya S; Garg, S K; Singh, Mohan; Kalpana, Duda (Journal of Agricultural Engineering, 2005)
Extrusion cooking of Soy-Sorghum blend with 5 level of blend ratio (5, 10, 15. 20 and 25% of Soybean in blend), 3 levels of barrel temperature (80, 90 and100 degree C) and 3 levels of feed moisture contents (15, 20 and 25%) in a Wenger x-5 single screw laboratory extruder were conducted for the preparation of ready to eat snack food. The effects of barrel temperature, initial feed moisture content and blend ratios on properties like sectional expansion index, bulk density and crispness of extruded products were studied. Response surface methodology was used to optimize the process parameter for the development of the best product. The analysis of data indicated that all the process parameters had significant effect on physical properties.